Investigating the causal role of cellular senescence-related genes in preeclampsia: a multi-omics Mendelian randomization study with differential expression analysis - Zhu, Hao; Yu, Yi; Wang, Jue; Wang, Chengjie; Liu, Zhenzhen; Zhang, Xiaoyue; Hu, Rong; Gu, Weirong (Frontiers in Endocrinology, 2025)
BackgroundThe causal role of cellular senescence in preeclampsia pathogenesis is not fully established. This study aimed to systematically prioritize key senescence-related genes potentially driving preeclampsia using a Mendelian randomization (MR) framework.ResultsWe integrated genome-wide association studies (GWAS) of preeclampsia with expression, methylation, and proteomic quantitative trait loci (eQTLs/mQTLs/pQTLs) data for 866 senescence-related genes. Summary-data-based MR (SMR) coupled with the HEIDI (Heterogeneity in Dependent Instruments) test were used to assess causal associations and pleiotropy. Colocalization analysis evaluated shared genetic variants between QTLs and preeclampsia GWAS signals. Significant MR findings were explored for replication in an independent GWAS cohort (GCST90301704). Preliminary experimental support involved RT-PCR analysis of candidate genes in placental tissues from 10 preeclampsia patients and 5 gestational age-matched (34–38 weeks) healthy controls. Integration of SMR/HEIDI tests and colocalization (PPH4 > 0.5) prioritized 12 eQTLs, 62 mQTLs, and 2 pQTLs linked to preeclampsia. mQTL-eQTL analysis implicated methylation-regulated expression of ATG16L1, PMVK, and MAP3K14, offering valuable hypotheses for mechanistic studies.ConclusionPlacental RT-PCR showed upregulated ATG16L1 and downregulated PMVK, MAP3K14, NSUN2, and CDC25A in preeclampsia. Key genes (ATG16L1, PMVK, MAP3K14, NSUN2, CDC25A) link cellular senescence to preeclampsia, offering insights for mechanistic studies and therapeutic targeting.